Cerebral blood flow velocity response induced by a 70-hPa Valsalva manoeuvre associated with normo-and hypergravity in humans - Ossard, Gérard; Clère, Jean-Michel; Kerguélen, Michel; Melchior, Frauke; Seylaz, Jacques (European journal of applied physiology, 1996)
Anti-G straining manoeuvres, derived from the Valsalva manoeuvre (VM), are physiological methods for protecting fighter pilots against positive accelerations (+Gz). The aim of this study was to investigate the effects of a standard VM on cerebral haemodynamics, in normo- and hypergravity. In six healthy male volunteers, we investigated the cerebral blood flow velocity response induced by a 10-s, 70-hPa (52.5 mmHg) VM, under normogravity, + 2, + 3 and + 4 Gz acceleration plateaus. Mean blood flow velocity ($$\overline {{\text{BFV}}} $$) in middle cerebral artery was monitored by transcranial Doppler velocimetry. In normogravity, no significant variation in $$\overline {{\text{BFV}}} $$was observed at the onset of VM. After a maximal period of 1.2 s, while VM was sustained, $$\overline {{\text{BFV}}} $$decreased significantly (P < 0.05). Following the end of the manoeuvre $$\overline {{\text{BFV}}} $$did not change significantly. When the expiratory pressure had returned to the control value, $$\overline {{\text{BFV}}} $$was transiently increased (P < 0.05) before returning to control values. During hypergravity, $$\overline {{\text{BFV}}} $$was significantly decreased at + 3 and + 4 Gz (P < 0.05) before the onset of VM. While performing VM under + Gz, the main difference compared to the normogravity condition was a significant increase of $$\overline {{\text{BFV}}} $$(P < 0.05) at the onset of the manoeuvre. Our findings would suggest that when performed under + Gz stress, a 70-hPa VM can transiently improve cerebral haemodynamics. However, when VM is sustained for more than 1.2 s it results in a lasting decrease of cerebral perfusion which may lower + Gz tolerance.